Annual Plan 2000-2001 Volume I (Part I) Government of Uttar Pradesh State Planning Commission - Planning Commission (Planning Commission, 2000)
With one more year left for the expiry of Ninth Five Year Plan (1997-2002), the Annual Plan 2000-2001 assumes special significance for the State. The proposals of this Plan should be viewed in the background of the levels of development of the State, both economic and social, an overall view of the achievement of the State in the first three years of the Plan from 1997-98 to 1999-2000, and the picture likely to emerge at the end of the Plan. The levels of development of the State achieved at the end of the Eighth plan in 1996-97 were far lower than most of the States of the country, leaving a far greater gap to be bridged in the succeeding plans requiring far greater resources and efforts than what the State could hope to mobilize on its own.
Government of Uttar Pradesh State Planning Commission